2022
DOI: 10.1155/2022/6732150
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Atrial Fibrillation from ECG Signal Using Hybrid Deep Learning Techniques

Abstract: In cardiac rhythm disorders, atrial fibrillation (AF) is among the most deadly. So, ECG signals play a crucial role in preventing CVD by promptly detecting atrial fibrillation in a patient. Unfortunately, locating trustworthy automatic AF in clinical settings remains difficult. Today, deep learning is a potent tool for complex data analysis since it requires little pre and postprocessing. As a result, several machine learning and deep learning approaches have recently been applied to ECG data to diagnose AF au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…First, we defined the performance metrics as given in previous studies [23][24][25][26][42][43][44][45]. Precision, the percentage of labels that were correctly predicted is represented by the model precision score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we defined the performance metrics as given in previous studies [23][24][25][26][42][43][44][45]. Precision, the percentage of labels that were correctly predicted is represented by the model precision score.…”
Section: Resultsmentioning
confidence: 99%
“…These cross-subject problems with large and complex data can be handled in a much better way by employing deep learning techniques [10,21]. The studies reported in [22][23][24][25][26] quantified EEG features to recognize neurological deteriorations according to the task because of stroke and estimate the biomarkers to differentiate between healthy adults and ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 99%